Penerapan Input Eksternal Rendah Dalam Budidaya Padi Sehat di Kelompok Tani Soponyono I Kabupaten Musi Rawas - Safriyani, Etty; Murniati, Nely; Karyono, Teguh (Gapenas Publisher, 2025)
This community service activity with the healthy plant cultivation (bts) method aims to reduce dependence on the use of inorganic fertilizers in rice cultivation, using environmentally friendly technologies including using superior rice variety seeds, improving soil fertility with organic fertilizers and agricultural lime, gradual soil processing, planting refugia, namely artificial microhabitats for the conservation of natural enemies and controlling pests and diseases in an integrated manner to produce healthy rice, a sustainable environment, and products that are safe for consumption and the use of rice straw waste for making fermented feed and organic compost fertilizer. The community partnership program partners are: Soponyono 1 farmer group, Tanah Periuk Village, Muara Beliti District, Musi Rawas Regency, South Sumatra. Some of the obstacles faced by this farmer group include: 1). Dependence on chemical fertilizers and pesticides, 2). Pest attacks and plant-disturbing organisms that are difficult to control, 3). Declining agricultural productivity, 4) The lack of optimal utilization of rice straw for animal feed and organic compost fertilizer. Therefore, an approach is needed that is able to maintain production consistency without being constrained by seasons, pests and soil quality. The innovation implemented is the development of agriculture with low-input technology and efforts towards sustainable agricultural development. The approach methods used are extension and training, as well as mentoring and empowerment of the community (farmer groups). The results of this community service activity show that the communities involved can adopt and apply it in their agricultural land and there is an increase in agricultural productivity